Nanoparticle Induced Conformational Switch Between α-Helix and β-Sheet Attenuates Immunogenic Response of MPT63 - Sannigrahi, Achinta (Langmuir : the ACS journal of surfaces and colloids, 2018)
Although significant efforts have been devoted to develop nanoparticle-based biopharmaceuticals, it is not understood how protein conformation and nanoparticle surface modulate each other in optimizing the activity and/or toxicity of the biological molecules. This is particularly important for a protein, which can adopt different conformational states separated by a relatively small energy barrier. In this paper, we have studied nanoparticle binding-induced conformational switch from β-sheet to α-helix of MPT63, a small major secreted protein from Mycobacterium tuberculosis and a drug target against Tuberculosis. The binding of magnetite nanoparticles to MPT63 results in a β-sheet to α-helix switch near the sequence stretch between the 19th and 30th amino acids. As a consequence, the immunogenic response of the protein becomes compromised, which could be restored by protein engineering. This study emphasizes that conformational stability toward NP surface binding may require optimization involving genetic engineering for development of a nanoparticle conjugated pharmaceutical